Cell–cell junction gene signatures as subtype-specific prognostic biomarkers in breast cancer - Hayato Ishii; Kyoka Nishiyama; Ayaka Nakahara; Shoma Tamori; Shigeo Ohno; Kazunori Sasaki; Kazunori Akimoto (PLoS ONE, 2026)
Cell–cell junctions (CCJs) are essential for maintaining epithelial integrity, and adhesion-related molecules have long been implicated in breast cancer progression. However, the subtype-specific prognostic significance of CCJ-related gene expression patterns within individual intrinsic breast cancer subtypes has not been systematically characterized. We analyzed 179 genes annotated to the Gene Ontology term “cell–cell junction organization” (GO:0045216) across intrinsic breast cancer subtypes using the METABRIC and The Cancer Genome Atlas (TCGA) datasets. Subtype-specific prognostic CCJ genes were identified using multivariate Cox proportional hazards models for disease-specific survival and integrated into CCJ gene expression signatures. The prognostic performance was validated in an independent cohort (SCAN-B). Elevated CCJ signature scores were associated with poorer survival across subtypes, with particularly strong effects in Luminal B (LumB) and Basal-like (Basal) tumors. Person-year analyses indicated that high CCJ scores predicted an increased incidence of early recurrence (0–5 years) in these aggressive subtypes. Pathway enrichment analyses revealed that high-score tumors exhibited upregulation of extracellular matrix organization and matrisome-related pathways. Single-cell RNA sequencing further demonstrated that LumB CCJ genes (e.g., PARD6B , CDH3 ) were predominantly expressed in tumor epithelial cells, whereas the Basal CCJ signature reflected contributions from epithelial (e.g., MARVELD2 ) and endothelial (e.g., RAMP2 ) cells. Collectively, CCJ signatures stratify prognosis and capture subtype-specific cellular and microenvironmental features in breast cancer.